2022
DOI: 10.1177/03913988221121355
|View full text |Cite
|
Sign up to set email alerts
|

The ProtekDuo for percutaneous V-P and V-VP ECMO in patients with COVID-19 ARDS

Abstract: Objective: The ProtekDuo with oxygenator mimics veno-venous (V-V) extracorporeal membrane oxygenation (ECMO) in veno-pulmonary (V-P) configuration. We have recently developed a new configuration by utilizing a 25 Fr multistage femoral venous drainage cannula and by returning oxygenated blood through both lumina of the double lumen ProtekDuo cannula (V-VP configuration), thereby creating partial right ventricular bypass and oxygenated blood flow of up to seven LPM. We investigated our experience with V-P and V-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In contrast to the above-mentioned studies where V-P ECMO was the initial configuration, the most recent study by the group of Maybauer showed that V-P or V-VP ECMO configuration was established weeks after the onset of ARDS and ECMO initiation. This selected group of patients still displayed good outcomes with a survival rate of 67% 12 and the ProtekDuo has been shown to be a game changer when used in patients with ARDS secondary to COVID-19. 13 However, the available data is scarce and may have institutional bias.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to the above-mentioned studies where V-P ECMO was the initial configuration, the most recent study by the group of Maybauer showed that V-P or V-VP ECMO configuration was established weeks after the onset of ARDS and ECMO initiation. This selected group of patients still displayed good outcomes with a survival rate of 67% 12 and the ProtekDuo has been shown to be a game changer when used in patients with ARDS secondary to COVID-19. 13 However, the available data is scarce and may have institutional bias.…”
Section: Discussionmentioning
confidence: 95%
“…We calibrated the flows based on end-organ dysfunction and resolution of liver failure and renal failure. There is are reports of V-VP ECMO configuration that were used for a partial duration of total ECMO support [18][19][20]. In these cases, described by Maybauer and colleagues, all patients were either on V-V ECMO or V-P ECMO before the configuration was changed to V-VP ECMO without any complications.…”
Section: Discussionmentioning
confidence: 99%
“…Given this understanding, we followed the strategy of deploying RV mechanical circulatory support while simultaneously protecting the pulmonary circulation from high continuous flow overcirculation and providing flow through the RV using a partial RA flow Veno-venopulmonary artery (V-VP) ECMO strategy. Previously, this strategy has been used in short temporary duration, however; we report one of the first novel case of a near entire ECMO duration using a protected RV protected, pulmonary circulation partial flow, oxygenated Veno-venopulmonary (V-VP) RVAD strategy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…ECMO is an intervention that allows for either cardiac-, respiratory-, or combined cardiorespiratory support for patients who cannot be managed with conventional treatment strategies. 2 …”
Section: Introductionmentioning
confidence: 99%